Student wellbeing: Living alone and psychological distress among university students during the COVID-19 pandemic; a descriptive cross-sectional study in Northern Norway - Diab, Katrine Jonna (UiT Norges arktiske universitet, 2022)
Mental health issues have recently received increased awareness worldwide. Psychological distress refers to non-specific symptoms of anxiety, stress and depression and is indicative of impaired mental health. Students have been identified as an especially vulnerable group, with estimated 1 in 5 students affected by mental disorders. The novel COVID-19 pandemic and the effects of restrictions has been linked with increased levels of psychological distress and loneliness among students. The objective of this master thesis was to describe and investigate the relationship between psychological distress and living alone amongst students a year into the pandemic. Entry data from an ongoing pilot study project was used as a descriptive cross-sectional study. 117 students from the Arctic University of Norway volunteered for this study and 113 was included in the analyses. The outcome was psychological distress measured by an edited version of the CORE-OM tool (CORE-28), and the exposure was living alone. The relationship between psychological distress and living alone was explored by different statistical analyses. Other possible factors associated with psychological distress were investigated as well. Results showed an overall CORE-28 score of 1.67, indicating a moderate level of psychological distress amongst the students. The findings indicated that there was a higher level of psychological distress amongst those living alone, compared to those living with others, however, the estimates were not strong, even when adjusting for potential confounders. Only the group of students living in a room in a block had a large effect size and significant difference in means with a higher level of psychological distress found in those living alone. In conclusion, this study found an overall moderate level of psychological distress among students in Northern-Norway a year into the COVID-19 pandemic. There was an observed difference in level of psychological distress between those living alone and those living with others. However, ...